An Analysis of Factors Influencing Customers’ Willingness to Participate in Value Co-Creation of Indonesian Denim Brand Community (Case Study: Darahku Biru) - Avila Chrisdira, Vanessa; Rahmani Qastharin, Annisa; Mayangsari, Lidia (KnE Social Sciences, 2020)
The problem statement relies on how fashion industry’s positive trends affect fashion brands like Sukku Collective to compete with their competitors. A number of studies mentioned that building a profitable relationship between a firm and its customers to create value, or well-known as value co-creation, is a proven way for fashion brand owners to innovate and differentiate the brand in the market. Since participation is the key performance of brand community, the aim of this thesis is to study what factors affecting customers’ motivation to participate in brand community’s value co-creation of Indonesian denim brand community. In order to comply this objective, the author uses Darahku Biru, the first and biggest denim brand community in Indonesia. The variety of members and the size of brand community will help the researcher to learn about customers’ willingness to participate in value co-creation of denim brand community in general scope. In this study, the researcher developed seven hypothesis to analyze the influence factors. Data was collected using online questionnaire which was distributed to 133 Darahku Biru’s members using convenience sampling. The data were analysed using Multiple Linear Regression to identify the correlation. Based on the analysis, only community atmosphere and community experience have significant influence to customers’ willingness to participate in brand community’s value co-creation. The findings is expected to help fashion business owners and marketers to increase the effectiveness of brand community and revitalize the existing brand community. Keywords: Value Co-Creation, Customer Involvement, Brand Community, Competitive Advantage